Electron Transport-Linked Compared with Proton-Induced ATP Generation in Thiobacillus novellus - Cole, J. S. (1973)
The apparently soluble electron-transport system, that does not sediment when centrifuged at 144,000 × g or 300,000 × g for 3 hr, catalyzes oxidative phosphorylation with an efficiency comparable to that of an intact mitochondrial system. While the proton-induced phosphorylation occurs in whole cells, crude cell-free extracts, and supernatants from low-speed centrifugation, it does not occur in either the 144,000 or 300,000 × g supernatant fractions. The data show that oxidative energy can be conserved as ATP under conditions that are incompatible with the basic postulate of the chemiosmotic hypothesis.